Metformin in SARS-CoV-2 infection - Pedrosa, Ana Realista (2023)
SARS-CoV-2 infection has been a major threat to human health and a huge challenge to Medicine. In only two years, COVID-19 affected >350 million people, causing >5.6 million deaths. Chronic inflammatory states, such as diabetes or obesity, are known risk factors for COVID-19 poorest outcomes, with higher risk for disease severity and greater mortality. Metformin remains on the first line of the management of hyperglycemia in type 2 diabetes. Through its anti-inflammatory and immunomodulatory mechanisms, metformin appears as an opportunity to control the dysregulated cytokine storm secondary to SARS-CoV-2 infection. Recent studies point towards a potential protective role of metformin in the course of COVID-19, showing that current or previous treatment with metformin associates with better outcomes.